KETIMPANGAN PAPARAN BAHASA DAN DAMPAKNYA TERHADAP PEMEROLEHAN BAHASA ANAK USIAN 10 TAHUN DALAM SUKU BATAK TOBA-JAWA - Pebri Peronika Sinaga; Rani Julianti Butarbutar; Yensika Putri Sinurat; Garenta Viandia Nainggolan; Angelica Christiani Tamba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the impact of exposure imbalance on the language abilities of a 10-year-old child (a case study of Dimas Siregar) within a multilingual family (Batak Toba and Jawa) in Medan. A descriptive qualitative method was employed, utilizing interviews with both the child and Dimas acquired Batak Toba as his parents. The results indicate that Dimas acquired Batak Toba as his first language (B1) from the age of one,a process predominantly influenced by the father`s active involvement and the family`s patrilineal system. Conversely, Jawa (the mother`s language) is understood at a level a\of only about 40% due to minimal exposure. Upon reaching school age, the child began acquiring Indonesian as a second language (B2) through formal education and social interaction. From psycholinguistic and sociolinguistic perspectives, the subject falls into the category of an early consecutive, exhibiting an imbalance in usage where BataK Toba dominates the informal or family dominan, while Indonesian dominates the academic sphere. The primary factors driving this imbalance are the frequency of linguistic input from the urban sociocultural environment and the role of family strategies in determining the primary language used at home.